ANALISIS KONTEN PENDIDIKAN HATI NURANI DALAM AKUN INSTAGRAM @TKEKSPERIMENTAL - Borromeus Mulyatno, Carolus (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
This qualitative research aims to explore and analyze the content of conscience learning in Mangunan's @tkesperimental Instagram account. The method used in this research is ethnographic method. The theoretical framework used to formulate data collection instruments and analyze them is Y.B. Mangunwijaya's thoughts on conscience education. The results of this study show that conscience education is programmed and implemented in Mangunan Experimental Kindergarten. In the Intagram posts @tkesperimental during January 2024, there are three components of conscience education which include learning activities of solidarity, caring for others and caring for the environment. The process of conscience education that is carried out collaboratively is directed at the personal development of students to grow into explorative, creative and integral persons. This is in line with Y.B. Mangunwijaya's idea that learning activities are designed based on a clear educational vision and implemented collaboratively for the development of integral persons asÂ  social beings who care about each other and areÂ  responsible for preserving the environment.